Pure theory of the federal funds rate - Stefan Homburg (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
While the target federal funds rate represents a policy instrument, the effective federal funds rate is determined in a competitive interbank market. The paper proposes a theory of its determination. This yields a specific term structure of interest rates, an account of why the money multiplier approach failed, and a demonstration that interest on reserves does not change bank incentives.
Keywords: E43; E51; E58; G01; 330; federal funds rate; term structure of interest rates; excess reserves; money multiplier; zero lower bound